Pengembangan media pembelajaran e-comic berbasis pixton pada materi penjumlahan dan pengurangan pecahan - Eri Triyana Nuraeni; Saputra, Erwin Rahayu; Apriani, Ika Fitri (COLLASE (Creative of Learning Students Elementary Education), 2025)
Abstrack This research aims to develop pixton-based e-comic learning media against the background of limited use of learning media, therefore students tend to lack understanding of mathematics learning because educators who teach still use monotonous learning media, so they get bored. Technology-integrated learning media is believed to be a solution that can be used by educators to help students in the learning process, especially in elementary schools. The research method used in this research is the ADDIE method with five stages, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) (Evaluation). The data collection techniques used were interviews, observations and documentation studies. Based on the results of the development of learning media based on validation results, media experts show a percentage of 92.5% (very feasible), material experts with a percentage of 86.6% (very feasible), pedagogical experts with a percentage of 75% (feasible), user experts with a percentage 80% (feasible), Apart from that, the teacher response reached a percentage of 80% (very practical), and the student response reached 89.2% (very practical) at SDN Kalapadua and the percentage of student responses was 90.8% at SDN 6 Manonjaya, second This percentage also falls into the very practical category. So it can be concluded that this e-comic learning media is practical and suitable for use in learning. Keywords: Pixton, E-Comic, Math. Abstrak Penelitian ini bertujuan untuk mengembangan media pembelajaran e-comic berbasis pixton dengan latar belakang adanya keterbatasan penggunaan media pembelajaran oleh karena itu peserta didik cenderung kurang memahami pembelajaran matematika karena pendidik yang mengajar masih menggunakan media pembelajaran yang monoton, sehingga bosan. Media pembelajaran yang terintegrasi teknologi diyakini menjadi penyelesaian yang dapat digunakan oleh pendidik untuk membantu peserta didik dalam proses pembelajaran, terutama di sekolah dasar. Metode penelitian yang digunakan pada penelitian ini yaitu metode ADDIE dengan lima tahapan yaitu (1) Analisis (Analysis), (2) Desain (Design), (3)Pengembangan (Development), (4) Implementasi (Implementation), dan (5) Evaluasi (Evaluation). Teknik pengumpulan data yang digunakan yaitu wawancara, bservasi dan studi dokumentasi. Berdasarkan hasil pengembangan media pembelajaran berdasarkan pada hasil validasi ahli media menunjukkan persentase sebesar 92,5% (sangat layak), ahli materi dengan presentase 86,6% (sangat layak), ahli pedagogik dengan presentase 75% (layak), ahli pengguna dengan presentase 80% (layak), Selain itu respon guru mencapai persentase 80% (sangat praktis), dan respon peserta didik mencapai 89,2% (sangat praktis) di SDN Kalapadua dan presentase respon peserta didik 90,8% di SDN 6 Manonjaya, kedua persentase tersebut juga termasuk kategori sangat praktis. Sehingga dapat disimpulkan bahwa media pembelajaran e-comic ini praktis dan cocok digunakan dalam pembelajaran. Kata Kunci: Pixton, E-Comic, Matematika.